2018
DOI: 10.1039/c8an00705e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Raman spectroscopy (esR) for distinguishing between the enantiomers of 2-butanol

Abstract: The first experimental application of enantioselective Raman spectroscopy (esR) is demonstrated using the example of the chiral alcohol 2-butanol. Samples of the neat enantiomers and the racemic mixture were analyzed in a self-built Raman set-up. The Raman spectrum allows the discrimination of the chemical species. It is shown that the optical rotation of a Raman peak with a small depolarization ratio can be measured. In addition, without any sample modification, e.g. chiral solvent, the enantiomers are distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The C═O stretching at 1795 cm À1 is different from the position of 1735 cm À1 in Figure S6C, which could be attributed to the formation of isomers (eg, pentanoic acid 1-methylpropyl ester). 52,53 The characteristic band of hydroxyl groups (-OH) from 2-butanol appears in the range from 3200 to 3500 cm À1 (see Figure S6B), 54 which is overlapped with the hydroxyl groups from water. 55…”
Section: In-situ Electrochemical Raman Studymentioning
confidence: 99%
“…The C═O stretching at 1795 cm À1 is different from the position of 1735 cm À1 in Figure S6C, which could be attributed to the formation of isomers (eg, pentanoic acid 1-methylpropyl ester). 52,53 The characteristic band of hydroxyl groups (-OH) from 2-butanol appears in the range from 3200 to 3500 cm À1 (see Figure S6B), 54 which is overlapped with the hydroxyl groups from water. 55…”
Section: In-situ Electrochemical Raman Studymentioning
confidence: 99%
“…for the on-line monitoring of synthesis processes of chiral drugs [120]. The approach was recently advanced with an automatized polarization-resolved Raman setup and coupled with chemometric analysis [119,121] which enabled enantiomeric differentiation of butan-2-ol [120,121]. Also, the enantiomeric fractions of the chiral molecule (5,6)-diphenyl-morpholin-2-one could be determined [119].…”
Section: Raman Optical Activity and Enantioselective Raman Spectroscomentioning
confidence: 99%
“…These limitations present water and ethanol as the most common solvents, making them less relevant for detecting chirality in organic crystals. A few methods are known for enantiomeric differentiation in their solid form such as second harmonic generation, CD, and vibrational CD. , However, some of the mentioned methods are time-consuming, expensive, experimentally complicated, require molecular labeling or addition of chemical agents, and eventually turn out to be impractical in terms of time-resolution for process monitoring …”
Section: Introductionmentioning
confidence: 99%
“…There are recent reports where the Raman enhancement technique is used for enantiomeric discrimination in solution, which requires special sample preparation. Moreover, these reports make use of asymmetries of C–H, C–S–C, and G and D bands of graphene rather than a chiral molecule. ,, A detailed comparison of different types of Raman studies conducted toward enantiomeric discrimination can be found in the Supporting Information section under Table S1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation